A database of chief financial officer turnover and dismissal in S&P 1500 firms, 2000–2022 - Zhang, Ziheng; Mount, Matthew P.; Zhang, Stephen X. (Strategic Management Journal, 2025)
Abstract Research Summary Understanding the antecedents and consequences of executive turnover is an important topic in strategy research. Yet, due to limitations in data availability, we know little about the turnover and dismissal of executives beyond the CEO. To address this, we develop an open access database on CFO turnover and dismissal—given the unique interface CFOs form with CEOs as strategic partners—in S&P 1500 firms between 2000 and 2022. We search for media documentation of CFO turnover events and code for various types of departure with supporting evidence. We compare our CFO database with an open access CEO database and show distinct patterns of exit and interdependence between CFO and CEO departure. The results reveal important directions for strategy scholarship. The database is available on the OSF platform ( osf.io/fh248/?view_only=2c62d6eb59bd433496ce101689df3adc ). Managerial Summary CFOs are key executives who shape the firm's strategy with CEOs. Consequently, understanding why CFOs leave their jobs and how this impacts the firm is important. Yet, the reasons why CFOs leave their jobs are rarely captured in existing databases. To address this, we develop an open access database documenting various types of CFO turnover and dismissal in S&P 1500 firms from 2000 to 2022. We establish a robust coding protocol and describe how we develop our database. We further explore how our CFO database contributes to the literature by comparing it with an open access CEO database; highlighting new lines of research and questions that it can stimulate. The database is available on the OSF platform ( osf.io/fh248/?view_only=2c62d6eb59bd433496ce101689df3adc ).